An acoustic pressure pipette aspiration method for isotropic materials - Maghzinajafabadi, M.; Lamprecht, R.; Döllinger, Michael; Semmler, Marion; Sutor, Sutor (Journal of Physics: Conference Series, 2019)
A measurement setup is presented as a method to determine the elasticity modulus of both artificial and real tissue as a function of frequency. The future goal at the end is to develop and validate the method to measure the elasticity modulus of ex vivo cadaver animal vocal folds over the human phonation frequency range. In the present study, we investigate an innovative acoustic pressure pipette aspiration technique to measure the material characteristic of an isotropic silicone specimen with similar characteristics as human vocal folds. With the aim of ensuring reliable results, we test our method on different mixtures of silicone rubber. Four silicone samples with different consistencies were tested over a frequency range of 50 -500Hz. Influence of vibrometer laser spot location in an enclosed area on the sample surface was investigated by repeating the measurements ten times. The results show only small standard deviations demonstrating the potential of the acoustic pressure pipette aspiration technique for material characterization.
CRIS-Team Scopus Importer:2020-02-21